The Effectiveness of Fuzzy-SAW Method for the Selection of New Student Admissions in Vocational High School - Lestari, Pashatania Fitri Indah; Prabowo, Tito Tri; Utomo, Wahyu Mulyo (Universitas Negeri Malang, 2020)
New student admission activities are routine activities carried out by vocational high schools every year to get the best students. A method is needed that can be used as a means of screening to select students based on their abilities and fields that are in accordance with the characteristics of students. This study uses the Fuzzy-SAW Method which is carried out through 3 stages, namely preparation of the components of the situation, the analysis and synthesis of information. The use of this method is expected to be able to help and provide the best decisions in the acceptance of new students.